Towards sustainable Summer comfort - Laia, Carlos (2010)
There is a growing energy demand for cooling in European buildings. It is expected that the cooled floor area will be four times higher in 2020 when compared with 1990 figures. Cooling is already the energy use in the building sector with the highest increase rate. This evidence is not contributing to the overall objective of reduction CO2 emissions. The conventional answer to this problem is to improve of the energy efficiency of cooling. However, this strategy showed limited results in terms of saving energy and reducing greenhouse gas emissions. In fact, cooling can be avoided (or the need to use energy for cooling) or significantly reduced without risking summer thermal comfort for building occupants, having thus the potential to achieve substantial reductions in energy demand. However, avoidance or even major reduction of cooling implies a new approach in building design, construction and operation phases. Different scientific and technological advances shall coherently be used and be offered to building promoters or building owners as a new service. The new adaptive comfort theory, the possibility for local adaptation for building users and facilities, the capability to intervene in the surrounding urban environment, the use of mature passive cooling solutions, of renewable energy sources and high efficiency lighting (reducing internal heat gains) are some examples of the techniques to be integrated in the new approach. Such a service should integrate different skills and competences as well as different kind of systems and equipments, from architects, building consultants and engineers, from solar shading devices, integrators of passive solutions and suppliers of very efficient lighting and office equipment.